2003
DOI: 10.1523/jneurosci.23-29-09529.2003
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Signaling of Estrogen in Hypothalamic Neurons Involves a Novel G-Protein-Coupled Estrogen Receptor that Activates Protein Kinase C

Abstract: Classically, 17beta-estradiol (E2) is thought to control homeostatic functions such as reproduction, stress responses, feeding, sleep cycles, temperature regulation, and motivated behaviors through transcriptional events. Although it is increasingly evident that E2 can also rapidly activate kinase pathways to have multiple downstream actions in CNS neurons, the receptor(s) and the signal transduction pathways involved have not been identified. We discovered that E2 can alter mu-opioid and GABA neurotransmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
502
3
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 411 publications
(533 citation statements)
references
References 77 publications
22
502
3
3
Order By: Relevance
“…Interestingly, ER-X also has a distinct pharmacology in that 17α-estradiol is as equipotent as E 2 in activating the MAP kinase pathway [15,30]. However, we did not see any effects of 17α-estradiol on the GABA B response [17] or the μ-opioid response [21]. Similarly, Gu and Moss found that 17α-estradiol did not mimic the actions of E 2 in the hippocampus to potentiate the glutamate (kainate)-mediated currents in CA1 pyramidal neurons [35].…”
Section: Mer Is a Gpcr In Hypothalamic Pomc Neuronscontrasting
confidence: 67%
See 4 more Smart Citations
“…Interestingly, ER-X also has a distinct pharmacology in that 17α-estradiol is as equipotent as E 2 in activating the MAP kinase pathway [15,30]. However, we did not see any effects of 17α-estradiol on the GABA B response [17] or the μ-opioid response [21]. Similarly, Gu and Moss found that 17α-estradiol did not mimic the actions of E 2 in the hippocampus to potentiate the glutamate (kainate)-mediated currents in CA1 pyramidal neurons [35].…”
Section: Mer Is a Gpcr In Hypothalamic Pomc Neuronscontrasting
confidence: 67%
“…Notably, AC VII has a potential binding site for PKCδ that is not present in the sequences of the other adenylyl cyclases, which would allow PKCδ to directly phosphorylate AC VII [43]. In our study, we have shown that hypothalamic POMC neurons express AC VII transcripts [17]. Moreover, internal perfusion of BIS completely blocked the inhibition of the baclofen response by E 2 but did not attenuate the inhibition of the baclofen response by forskolin applied via bath perfusion, suggesting that PKC activation is upstream of PKA activation.…”
Section: Mer Is a Gpcr In Hypothalamic Pomc Neuronsmentioning
confidence: 65%
See 3 more Smart Citations